Nano-grain-size lead-free ceramic material with local structure reinforced design and preparation method of nano-grain-size lead-free ceramic material
The nano-grain-sized lead-free ceramic material designed through local structure strengthening solves the problem that lead-free relaxation ferroelectric ceramics are difficult to improve both energy storage density and efficiency under high electric fields, and achieves high energy storage density and high efficiency ceramic materials.
Patent Information
- Application Number
- CN202411695215.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The energy storage density and efficiency of lead-free relaxation ferroelectric ceramics under high electric fields are difficult to improve, and they have performance limitations.
A lead-free ceramic material with nanocrystal size designed with local structure reinforcement is prepared by (0.7-x)BaTiO3-0.3Bi0.5Na0.5TiO3-xBa(Zn1/3Nb2/3)O3, and is prepared by ball milling, drying, calcining, sintering and ion sputtering gold-plating electrodes.
The energy storage density reaches 15.1 J cm-3 under high electric field, and the energy storage efficiency is stable at more than 85%, and it has excellent frequency, heat and cycle stability.
Smart Images

Figure CN119707480A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of dielectric energy storage ceramic materials, and in particular to a lead-free ceramic material with a nano-grain size and a local structure strengthening design and preparation thereof. Background Art
[0002] The growing material needs of mankind and the incomplete and insufficient development of energy are the major contradictions in the current energy industry. The concept of sustainable development urges scientists to use advanced energy storage technologies to achieve efficient storage and utilization of these energy resources. Among them, dielectric energy storage capacitors play a key role in pulse power systems and high-voltage applications, and the energy storage performance limitations of lead-free perovskite ferroelectric energy storage ceramics as core components hinder the development of devices towards miniaturization, intelligence and integration. Therefore, the research and development of new environmentally friendly and high-performance dielectric energy storage materials is particularly urgent.
[0003] However, the energy storage density and efficiency of existing barium titanate-based lead-free relaxor ferroelectric ceramics under high electric fields are in conflict, and it is impossible to improve both energy storage density and efficiency at the same time, and further improvement is needed. Summary of the invention
[0004] The technical problem to be solved by the present invention is the conflict between the energy storage density and efficiency of lead-free relaxor ferroelectric ceramics under high electric fields. Therefore, a lead-free ceramic material with nano-grain size and a preparation method with a local structure strengthening design is proposed, which can improve both the energy storage density and efficiency at a higher level.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] In the first aspect, a lead-free ceramic material with a nano-grain size and a local structure strengthening design is provided, wherein the chemical composition is (0.7-x)BaTiO3-0.3Bi 0.5 Na 0.5 TiO3-xBa(Zn 1 / 3 Nb 2 / 3 )O3.
[0007] In the present invention, 0.04≤x≤0.16, and x can be, for example, 0.04, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, or 0.16.
[0008] Preferably, 0.10<x≤0.14, more preferably 0.11≤x≤0.13.
[0009] More preferably, x=0.12.
[0010] Under the above preferred x scheme, its energy storage efficiency can be stabilized at more than 82%, and at 90 kV mm -1Under an electric field of 1.50 W, the energy storage density can reach 15.1 J cm -3 , the energy storage efficiency can reach 85%.
[0011] Preferably, the lead-free ceramic material has a nano-scale grain size.
[0012] Further preferably, the grain size of the lead-free ceramic material is 500-700nm, which is more conducive to the formation of polar nano-micro-regions; the grains are dense, the grain boundary density is increased, and the potential distribution is more uniform, thereby improving the breakdown field strength; the polarization reorientation stress is reduced, and the relative residual polarization intensity is increased, ultimately achieving high efficiency.
[0013] In a second aspect, a method for preparing the lead-free ceramic material with nano-grain size designed for local structural strengthening according to the first aspect is provided, comprising the following steps:
[0014] S1, according to (0.7-x)BaTiO3-0.3Bi 0.5 Na 0.5 TiO3-xBa(Zn 1 / 3 Nb 2 / 3 )O3 stoichiometric ratio of Bi2O3, Na2CO3, BaCO3, TiO2, ZnO and Nb2O5 powders are weighed, immersed in an organic solvent and ball milled once, the filtered slurry is dried and ground into powder, and then calcined once;
[0015] S2, after cooling the powder obtained by calcining S1 once to room temperature, adding a binder and grinding it into powder, and then pressing it into a shape;
[0016] S3, placing the sample obtained in S2 in a muffle furnace and heating it to 500-600°C for low temperature sintering to react and remove the binder; then heating it to between 1100-1300°C for high temperature sintering;
[0017] S4, polishing the ceramic sheet obtained after high-temperature sintering in S3, and then ion sputtering to plate a gold electrode.
[0018] Preferably, in S1, the conditions of the first ball milling include: a rotation speed of 300-400 rpm, and a time of not less than 8 hours. This preferred solution is more conducive to ensuring sufficient mixing between the raw materials and sufficient solid phase reaction; the particles are finer, which helps to form a more uniform microstructure in the subsequent sintering process; the ball-milled powder is more likely to form a dense structure during the pressing and sintering process, which is conducive to improving the mechanical strength of the ceramic material.
[0019] Preferably, the drying time is 2-3 hours.
[0020] Preferably, the conditions for the primary calcination include: a temperature of 800-900° C. and a time of 2-3 hours. This preferred solution is more conducive to improving the density of the ceramic and helps to maintain the single-phase structure of the material.
[0021] Preferably, in S1, the organic solvent is anhydrous ethanol. The amount of ethanol in S1 can be freely selected according to the volume of the container used and the grinding uniformity, as long as it is conducive to uniform grinding, and the ethanol will evaporate in the subsequent drying process.
[0022] Preferably, the binder in S2 is a polyvinyl alcohol aqueous solution with a mass fraction of 3%-5%.
[0023] Preferably, the mass ratio of the binder to the powder of S1 after the first calcination is 1:5-15. This preferred solution is more conducive to reducing the cracking of the pressed ceramic sheet during the sintering process and improving the density of the material.
[0024] Preferably, in S3, the low-temperature sintering time is 2-3 hours, and the high-temperature sintering time is 2-3 hours.
[0025] Preferably, the heating rates in the low-temperature sintering and high-temperature sintering stages are independently 4-6°C / min. This preferred solution is more conducive to controlling the growth rate of the grains, thereby obtaining a uniform grain size distribution; reducing the thermal stress inside the material, avoiding the internal stress concentration and crack formation of the material caused by rapid heating, and reducing the porosity.
[0026] Preferably, the high temperature sintering temperature in S3 satisfies: when 0.04≤x<0.08, the high temperature sintering temperature is 1160° C., and when 0.08≤x≤0.16, the high temperature sintering temperature is 1140° C. This preferred solution is more conducive to optimizing grain growth and forming a uniform microstructure.
[0027] Preferably, in S4, the polishing process includes: polishing on sandpaper to a thickness of 0.05-0.3 mm. This preferred solution is more conducive to improving breakdown, and only when a sufficiently high electric field is applied can subsequent ferroelectric instrument testing and energy storage testing be performed.
[0028] Further preferably, the particle size of the sandpaper is 400-800 Cw.
[0029] Preferably, the ion sputtering process in S4 includes: selecting a gold target as the target material, applying a current of 9-11 mA for 200-400 s when the vacuum is drawn to less than 10 Pa. This preferred solution can make the electrodes on the ceramic surface more uniform, thereby stabilizing and improving the breakdown electric field strength.
[0030] In a specific embodiment of the present invention, the preparation method comprises the following steps:
[0031] S1, according to (0.7-x)BaTiO3-0.3Bi 0.5 Na 0.5 TiO3-xBa(Zn 1 / 3 Nb 2 / 3 )O3 stoichiometric ratio Weigh Bi2O3, Na2CO3, BaCO3, TiO2, ZnO and Nb2O5 powders, soak them in anhydrous ethanol and grind them with a planetary ball mill. The filtered slurry is placed in a drying furnace for drying, poured out and ground into powder, and then placed in a crucible and heated in a muffle furnace for calcination;
[0032] S2, after the powder obtained by calcining S1 is cooled to room temperature, the powder is poured into a mortar, a binder is added, and the sample is ground into powder after it becomes a block, and then poured into a special mold and pressed into a disc;
[0033] S3, place the sample obtained in S2 in a muffle furnace and heat it to 550°C and keep it at this temperature for two hours to react and remove the binder. Then heat it to between 1100-1300°C and keep it at this temperature for two hours (all heating processes are at a rate of 5°C / min);
[0034] S4, polish the ceramic sheet sintered in S3 with sandpaper, plate gold on both sides by magnetron sputtering and polish off the gold plated on the side. In summary, a lead-free ceramic material with nano-scale grain size and high energy storage density and efficiency based on local structure strengthening design can be obtained.
[0035] The beneficial effects of the above technical solution of the present invention are as follows:
[0036] The present invention successfully developed a new lead-free energy storage ceramic material based on BaTiO3 (BT) through local structural design. This material exhibits excellent energy storage performance, including extremely high polarization change (ΔP = 49μC cm -2 ), high breakdown electric field (E B = 90kV mm -1 ) and excellent thermal stability, frequency stability and cycle stability. The energy storage density of this material reaches 15.1 J cm -3 ), and has made significant improvements in the field of BT-based lead-free bulk ceramics.
[0037] Specifically, the present invention adds an appropriate amount of Bi to the BT base. 0.5 Na 0.5 TiO3 and Ba(Zn 1 / 3 Nb 2 / 3 )O3, and with appropriate proportions of BaTiO3 and Ba(Zn 1 / 3 Nb 2 / 3)O3, can introduce a variety of different valence ions on the atomic scale through the local structure to enhance the random field, and coordinately design the local polymorphic distortion structure by regulating the polycrystalline phase transition temperature, realizing the gradual evolution of ceramics from nanodomains to microdomains and then to PNRs, significantly improving the breakdown field strength and energy storage performance of the material. The polarization displacement size and angular distribution were analyzed using spherical aberration electron microscopy, revealing the mechanism by which local diverse polarization configurations enhance polarization and thus optimize energy storage. This achievement clarifies the advantages of local structure design for the development of new lead-free ceramic materials that have both high energy storage capacity and high efficiency. Among them, under the same conditions, if Ba(Zn 1 / 3 Nb 2 / 3 )O3, will lead to the Curie temperature Tm not dropping to the room temperature, the relative residual polarization intensity is reduced, and the energy storage efficiency is reduced; if BaTiO3 and Ba(Zn 1 / 3 Nb 2 / 3 )Different O3 ratios will lead to large differences in grain size, which in turn leads to low maximum energy storage density. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a grain picture of the barium titanate-based relaxor ferroelectric ceramic prepared in Example 1, taken by SEM.
[0039] Figure 2 hysteresis loop diagram of the barium titanate-based relaxor ferroelectric ceramic prepared in Example 1 under different applied electric fields.
[0040] Figure 3 The barium titanate-based ceramics prepared in Example 1 are subjected to a 10 kV mm -1 Up to 90kV mm -1 The dotted line graph below shows the changes in energy storage density and efficiency.
[0041] Figure 4 The curve showing the change of the unipolar hysteresis loop of the barium titanate-based relaxor ferroelectric ceramic prepared in Example 1 with frequency.
[0042] Figure 5 The unipolar hysteresis loop of the barium titanate-based relaxor ferroelectric ceramic prepared in Example 1 varies with temperature.
[0043] Figure 6 The unipolar hysteresis loop of the barium titanate-based relaxor ferroelectric ceramic prepared in Example 1 varies with the number of cycles. DETAILED DESCRIPTION
[0044] The present invention aims to propose a lead-free ceramic material with nano-scale grain size and high energy storage density and efficiency based on local structure strengthening design and its preparation process. It belongs to the field of dielectric energy storage ceramic materials; its chemical composition is: (0.7-x)BaTiO3-0.3Bi 0.5 Na0.5 TiO3-xBa(Zn 1 / 3 Nb 2 / 3 )O3, 0.04≤x≤0.16. The breakdown field strength of the barium titanate-based ceramic of the present invention is as high as 90 kV mm -1 The relative remanent polarization intensity is as high as 49 μC cm -2 In terms of energy storage performance, it not only achieved 85% efficiency and 15.1 J cm -3 It has high energy storage density, charge and discharge capacity, and excellent frequency, thermal and cycle stability. The average grain size of the component with the best energy storage performance is about 630nm, which stands out among all barium titanate-based energy storage ceramics.
[0045] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0046] Embodiment 1:
[0047] The method of the present invention is used to prepare the component with the best energy storage performance 0.58BaTiO3-0.3Bi 0.5 Na 0.5 TiO3-0.12Ba(Zn 1 / 3 Nb 2 / 3 )O3, weigh 1.7474g Bi2O3, 0.3975g Na2CO3, 6.9069g BaCO3, 3.5143g TiO2, 0.1628g ZnO, 0.5316g Nb2O5 according to the chemical dosage ratio, pour into a nylon ball mill, add 150-200ml anhydrous ethanol and ball mill for not less than 8h, the planetary ball mill speed is set to 400 rpm, and the instrument is cooled for 5min every 15min. The filtered slurry is placed in a drying furnace for three hours, poured out and ground into powder, and then placed in a crucible and heated to 850°C in a muffle furnace for two hours. After cooling to room temperature, pour the powder into a mortar, drip a PVA binder (i.e., a polyvinyl alcohol aqueous solution with a mass fraction of 3%, and the mass ratio of the binder to the calcined powder is 1:10), grind the sample into powder after it becomes a block, pour it into a special mold, press it into a 10mm diameter disc under a pressure of about 300MPa, and then place it in a muffle furnace and heat it to 550°C and keep it warm for two hours to react the binder. Then heat it to 1140°C and sinter it at high temperature for two hours (all heating processes are at a rate of 5°C / min). The sintered ceramic sheet is polished to a thickness of 0.3mm on a 400Cw sandpaper, and 800Cw sandpaper is ground to 0.2mm. Finally, the magnetron sputtering method is used to plate gold electrodes on both sides in a chamber with an air pressure of less than 10Pa, and one side is plated with a point electrode. Each side is sprayed with gold and 10A is powered for 300s, and the gold plated on the side is polished off.
[0048] Figure 1 This is the grain morphology of the barium titanate-based ceramics obtained in this embodiment under a scanning electron microscope. According to statistics, the average grain size of 0.12 is 630nm;
[0049] Figure 2 The barium titanate-based ceramics prepared in this embodiment are -1 Up to 90kV mm -1 The unipolar hysteresis loop under the condition of 15.1 J cm-2 can be calculated to obtain the maximum recoverable energy storage density of 15.1 J cm-2. -3 , energy storage efficiency 85%, relative remanent polarization intensity 49 μC cm -2 ;
[0050] Figure 3 The barium titanate-based ceramics prepared in this embodiment are -1 Up to 90kV mm -1 The dotted line graph of energy storage density and efficiency changes below shows the stability of efficiency and the linear growth of energy storage density;
[0051] Figure 4 The unipolar hysteresis loop of the barium titanate-based relaxor ferroelectric ceramic prepared in Example 1 varies with frequency, indicating that the barium titanate-based ceramic prepared in this example has a high resistance to 45 kV mm -1 Temperature stability from room temperature 30℃ to 160℃.
[0052] Figure 5 The unipolar hysteresis loop of the barium titanate-based relaxor ferroelectric ceramic obtained in Example 1 changes with temperature. 0 times to 10 6 Cycle number stability under multiple cycles.
[0053] Figure 6 The curve of the unipolar hysteresis loop of the barium titanate-based relaxor ferroelectric ceramic prepared in Example 1 as a function of the number of cycles shows the unipolar hysteresis loop measured from the frequency stability of 1-200 Hz. Figure 4-Figure 6 It can be seen that its stability is quite excellent.
[0054] Embodiment 2:
[0055] The method of Example 1 is followed, except that the ceramic material composition is: 0.6BaTiO3-0.3Bi 0.5 Na 0.5 TiO3-0.1Ba(Zn 1 / 3 Nb 2 / 3)O3, and correspondingly according to the chemical dosage ratio, weigh 1.7474 grams of Bi2O3, 0.3975 grams of Na2CO3, 6.9069 grams of BaCO3, 3.5942 grams of TiO2, 0.1357 grams of ZnO, and 0.4430 grams of Nb2O5.
[0056] The test results show that the barium titanate-based relaxor ferroelectric ceramics prepared in this embodiment have a high thermal conductivity at 79 kV mm -1 Under an electric field of 1.50 W, the energy storage density reaches 12.9 J cm -3 , the energy storage efficiency reaches 86.8%.
[0057] Embodiment 3:
[0058] The method of Example 1 is followed, except that the ceramic material composition is: 0.56BaTiO3-0.3Bi 0.5 Na 0.5 TiO3-0.14Ba(Zn 1 / 3 Nb 2 / 3 )O3, and correspondingly according to the chemical dosage ratio, weigh 1.7474 grams of Bi2O3, 0.3975 grams of Na2CO3, 6.9069 grams of BaCO3, 3.4344 grams of TiO2, 0.1899 grams of ZnO, and 0.6202 grams of Nb2O5.
[0059] The test results show that the barium titanate-based relaxor ferroelectric ceramics prepared by this component have a high thermal conductivity at 72 kV mm -1 The energy storage density reaches 11.2 J cm -3 , the energy storage efficiency reaches 85.7%.
[0060] Embodiment 4:
[0061] The method of Example 1 is used, except that the high-temperature sintering temperature is 1160°C.
[0062] The test results show that the barium titanate-based relaxor ferroelectric ceramics prepared by this component have a high thermal conductivity at 85 kV mm -1 The energy storage density reaches 14.1 J cm -3 , the energy storage efficiency reaches 85.7%.
[0063] Comparative Example 1:
[0064] The method of Example 1 is followed, except that the ceramic material composition is: 0.7BaTiO3-0.3Bi 0.5 Na 0.5 TiO3 (i.e. x=0).
[0065] The test results show that the barium titanate-based relaxor ferroelectric ceramics prepared by this component have a high thermal conductivity at 10 kV mm -1Under an electric field of 1.50, the energy storage density reaches 1.29 J cm -3 , the energy storage efficiency reaches 16.6%.
[0066] Comparative Example 2:
[0067] The method of Example 1 is followed, except that the ceramic material composition is: 0.90BaTiO3-0.10Ba(Zn 1 / 3 Nb 2 / 3 )O3.
[0068] The test results show that the barium titanate-based relaxor ferroelectric ceramics prepared by this component have a high thermal conductivity at 10 kV mm -1 Under an electric field of 1.5 Å, the energy storage density reaches 0.32 J cm -3 , the energy storage efficiency reaches 55.5%.
[0069] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A lead-free ceramic material with nano-grain size and local structural strengthening design, characterized in that: Its chemical composition is (0.7-x)BaTiO3-0.3Bi 0.5 Na 0.5 TiO3-xBa(Zn 1 / 3 Nb 2 / 3 )O3, 0.04≤x≤0.
16.
2. The lead-free ceramic material according to claim 1, characterized in that: 0.10≤x≤0.14。 3. The lead-free ceramic material according to claim 1, characterized in that: Lead-free ceramic material has nano-scale grain size.
4. A method for preparing a lead-free ceramic material with a nano-grain size having a local structure strengthening design as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1, according to (0.7-x)BaTiO3-0.3Bi 0.5 Na 0.5 TiO3-xBa(Zn 1 / 3 Nb 2 / 3 )O3 stoichiometric ratio of Bi2O3, Na2CO3, BaCO3, TiO2, ZnO and Nb2O5 powders are weighed, immersed in an organic solvent and ball milled once, the filtered slurry is dried and ground into powder, and then calcined once; S2, after cooling the powder obtained by calcining S1 once to room temperature, adding a binder and grinding it into powder, and then pressing it into a shape; S3, placing the sample obtained in S2 in a muffle furnace and heating it to 500-600°C for low temperature sintering to react the binder; then heating it to between 1100-1300°C for high temperature sintering; S4, polishing the ceramic sheet obtained after high-temperature sintering in S3, and then ion sputtering to plate a gold electrode.
5. The preparation method according to claim 4, characterized in that: In S1, the conditions for the first ball milling include: a rotation speed of 300-400 rpm, and a time of not less than 8 hours; a drying time of 2-3 hours; and the conditions for the first calcination include: a temperature of 800-900° C., and a time of 2-3 hours.
6. The preparation method according to claim 4, characterized in that: In S1, the organic solvent is anhydrous ethanol; The binder in S2 is a polyvinyl alcohol aqueous solution with a mass fraction of 3%-5%, and the mass ratio of the binder to the powder after the first calcination of S1 is 1:5-15.
7. The preparation method according to claim 4, characterized in that: In S3, the low-temperature sintering time is 2-3 hours, and the high-temperature sintering time is 2-3 hours.
8. The preparation method according to claim 4 or 7, characterized in that: In S3, the heating rates in the low temperature sintering stage and the high temperature sintering stage are independently 4-6°C / min.
9. The preparation method according to claim 4, characterized in that: The temperature of the high temperature sintering in S3 satisfies: when 0.04≤x<0.08, the temperature of the high temperature sintering is 1160°C; when 0.08≤x≤0.16, the temperature of the high temperature sintering is 1140°C.
10. The preparation method according to claim 4, characterized in that: The ion sputtering process described in S4 includes: a gold target is selected as the target material, and when the vacuum degree is drawn to less than 10Pa, a current of 9-11mA is passed for 200-400s.
Citation Information
Patent Citations
Sodium bismuth titanate-barium titanate based lead-free relaxor ferroelectric energy storage ceramic and preparation method thereof
CN110451955A
Sodium bismuth titanate-based relaxor ferroelectric ceramic material with excellent energy storage performance and environmental stability and preparation method of sodium bismuth titanate-based relaxor ferroelectric ceramic material
CN116444265A